2015
DOI: 10.1055/s-0034-1385827
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Elastography and Scintigraphic Imaging After Thermal Microwave Ablation of Thyroid Nodules

Abstract: !Purpose: The aim of this study is to evaluate structural alterations of thyroid tissue after microwave ablation using elastography and scintigraphic imaging to investigate the applicability of these diagnostic methods for follow-up. Materials and Methods: 35 patients with 39 thyroid nodules were evaluated using elastography and scintigraphic imaging before and after ultrasound-guided microwave ablation. Elastography was analyzed according to color-coded output and results were classified using a fourfold elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It has been shown that tracer uptake after MWA ablation and during the follow-up was significantly reduced in the ablated tissue. Further research is necessary to establish the real role of scintigraphic imaging in follow-ups after MWA is used in the treatment of benign thyroid nodules [83,84].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…It has been shown that tracer uptake after MWA ablation and during the follow-up was significantly reduced in the ablated tissue. Further research is necessary to establish the real role of scintigraphic imaging in follow-ups after MWA is used in the treatment of benign thyroid nodules [83,84].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…It is not known to what extent this technology may aid in the management of positron emission tomography/computed tomography (PET/CT)-positive thyroid incidentalomas [104,105]. The value of US elastography for treatment monitoring of TN during and after radiofrequency, microwave, or laser ablation has not been studied sufficiently [106-108]. The value of US elastography-guided FNA biopsy of TNs in reducing nondiagnostic results needs to be further evaluated [109].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…No significant differences between the changes of elasticity, echogenicity and vascularization after cMWA and uMWA were observed. Thermal ablation procedure leads to elevated tissue stiffness (elasticity change) due to protein denaturation and dehydration [15] , [23] . Feng et.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the target area and the volume of the nodule (14–16 G; small, medium or large), different probes can be used to achieve the target temperature of 60–80 °C (max. 140 °C) with an ablation field of 1–4 cm [14] , [15] , [16] . The frequency is automatically controlled with real-time temperature and reverse-power feedback during ablation to optimize ablation safety, efficiency, energy transfer, and predictability.…”
Section: Methodsmentioning
confidence: 99%